The Influence of Costs, Long at Sea and Prices on Fishermen's Income in Alor District - Junius Menase Sau Sabu; Maryanti Sofyan (Universitas Mercu Buana, 2022)
The purpose of this study was to determine the effect of cost, duration of fishing and price on income. The methodology of this research is multiple linear regression with quantitative methods and uses primary data with data collection techniques: observation, interviews, questionnaires and literature study. The data is then processed with the help of SPSS 25. The analysis technique is preliminary analysis, namely: descriptive statistics, instrument tests and classical assumption tests, then followed by further analysis, namely analysis of the coefficient of determination and hypothesis testing, namely t-test and F-test. The results of this study are: ( 1) Partially, costs have an effect on income with a significance value of 3.5% < 5%. (2) Partially the length of time at sea has an effect on income with a significance value of 0% < 5%. (3) Partially the price has an effect on income with a significance value of 0% < 5%. (4) Simultaneously cost, length of fishing and price affect income with a significance value of 0% < 5%. The conclusions of this study are: 1) the results of the study accept H1, H2, H3 and H4.